2009
DOI: 10.2134/jeq2008.0239
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of Soluble and Dispersible Lead, Arsenic, and Antimony in a Polluted, Organic‐rich Soil – Effects of pH Increase and Counterion Valency

Abstract: Liming is a common technique suggested for the stabilization of shooting range sites. We investigated the effect of an increase in pH on the mobilization of soluble and dispersible (colloidal) Pb, As, and Sb. Our hypothesis was that the addition of divalent cations counteracts the pH-induced mobilization of soluble and colloidal metal(loid)s. We determined soluble (operationally defined as the fraction < 10 nm obtained after centrifugation) and dispersible (filter cut-off 1200 nm) As, Pb, Sb, Fe, and C(org) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…This increase can be attributed to the increase in soil pH and/or soil P level due to biochar amendments (Table 1, 2). The sorption capacity of soils to negatively charged oxy-anions of As decreases with increasing soil pH, which causes the number of positively charged sites on minerals to decrease (Klitzke and Lang 2009;Wilson et al 2010). The increased phosphate anion as an analog to arsenate competes for binding sites at iron oxide surfaces in soils with arsenate and accordingly results in a desorption of As retained in soils (Cao et al 2003b;Jain and Loeppert 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This increase can be attributed to the increase in soil pH and/or soil P level due to biochar amendments (Table 1, 2). The sorption capacity of soils to negatively charged oxy-anions of As decreases with increasing soil pH, which causes the number of positively charged sites on minerals to decrease (Klitzke and Lang 2009;Wilson et al 2010). The increased phosphate anion as an analog to arsenate competes for binding sites at iron oxide surfaces in soils with arsenate and accordingly results in a desorption of As retained in soils (Cao et al 2003b;Jain and Loeppert 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Pierce and Moore (1980) demonstrated the specificity of the surface of iron hydroxides and the influence of pH in the As adsorption. In this way, significant desorption of As is observed with the rise of pH; in this case, the rise in pH is related to the decrease of the positive surface charge of the iron oxides, which facilitates the desorption of arsenate (Ghosh et al, 2006;Klitzke & Lang, 2009;Masscheleyn et al, 1991). Table 3.…”
Section: Evolution Of Arsenic Pollution Twelve Years After the Accidentmentioning
confidence: 99%
“…The presence of organic matter has been studied as a key factor in the desorption of arsenic from iron oxides, in this way, Redman et al (2002) found that the interaction between natural organic matter and hematite diminished the sorption of arsenate, promoting its mobility, and other authors considered that dissolved organic matter can mobilize arsenic from iron oxides, increasing the concentration of this element in the solution (Bauer & Blodau, 2006;Dobran & Zagury, 2006;Mladenov et al, 2010). Otherwise, significant desorption of As is observed with the rise in pH, in this case, the higher pH is related to the lower positive surface charge of the iron oxides, which facilitates the desorption of arsenate (Ghosh et al, 2006;Klitzke & Lang, 2009;Masscheleyn et al, 1991). In this chapter, we present a general overview of the current stage of As content in the soils after one of the most important accidents involving soil pollution in Spain in recent decades: the Aznalcollar mine spill (Seville, SW Spain) in 1998.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a rise in soil pH generally causes a release of anions such as As(V) from their adsorption sites. As pH increases, the number of positively charged sites on minerals decreases, which lowers the sorption capacity of negatively charged oxy-anions of As [34,35].…”
Section: Abiotic Factors Influencing the Speciation And Mobility Of Amentioning
confidence: 99%